Validation of measurement‐guided 3D VMAT dose reconstruction on a heterogeneous anthropomorphic phantom. (8th July 2013) - Opp, Daniel; Nelms, Benjamin E.; Zhang, Geoffrey; Stevens, Craig; Feygelman, Vladimir
Abstract : 3DVH software (Sun Nuclear Corp., Melbourne, FL) is capable of generating a volumetric patient VMAT dose by applying a volumetric perturbation algorithm based on comparing measurement‐guided dose reconstruction and TPS‐calculated dose to a cylindrical phantom. The primary purpose of this paper is to validate this dose reconstruction on an anthropomorphic heterogeneous thoracic phantom by direct comparison to independent measurements. The dosimetric insert to the phantom is novel, and thus the secondary goal is to demonstrate how it can be used for the hidden target end‐to‐end testing of VMAT treatments in lung. A dosimetric insert contains a 4 cm diameter unit‐density spherical target located inside the right lung ( 0.21 g / cm 3 density). It has 26 slots arranged in two orthogonal directions, milled to hold optically stimulated luminescent dosimeters (OSLDs). Dose profiles in three cardinal orthogonal directions were obtained for five VMAT plans with varying degrees of modulation. After appropriate OSLD corrections were applied, 3DVH measurement‐guided VMAT dose reconstruction agreed 100% with the measurements in the unit density target sphere at 3%/3 mm level (composite analysis) for all profile points for the four less‐modulated VMAT plans, and for 96% of the points in the highly modulated C‐shape plan (from TG‐119). For this latter plan, while 3DVH shows acceptable agreement with independent measurements in the unit density target, in the lung disagreement with experiment is relatively high for both the TPS calculation and 3DVH reconstruction. For the four plans excluding the C‐shape, 3 % / 3 mm overall composite analysis passing rates for 3DVH against independent measurement ranged from 93% to 100%. The C‐shape plan was deliberately chosen as a stress test of the algorithm. The dosimetric spatial alignment hidden target test demonstrated the average distance to agreement between the measured and TPS profiles in the steep dose gradient area at the edge of the 2 cm target to be 1.0 ± 0.7, 0.3 ± 0.3, and 0.3 ± 0.3 mm for the IEC X, Y, and Z directions, respectively. PACS number: 87.55Qr